Robust algorithm for gain-and-phase errors estimation against the direction deviations of calibration sources - Ding WANG; Hui YAO; Ying WU (Tongxin xuebao)
The direction deviations of the calibration sources would significantly degrade the calibration accuracy of array gain-and-phase errors.Aiming to this problem,a robust calibration algorithm for gain-and-phase errors against the location deviations was presented under the assumption that the prior probability distribution of the location deviation was known.The idea of the robust algorithm was based on subspace fitting criterion and Bayesian estimation theory framework.The gain-and-phase errors were obtained through calculating the eigenvector associated with the minimum eigenvalue of some real symmetric matrix without estimating the locations of calibration sources.The closed-form Cramér-Rao bound(CRB)for the unknown parameters was derived,and the asymptotic distributions of the robust algorithm as well as the Cheng method were also given in the presence of direction deviations.Both the theory analysis and the simulation experiments validate that the asymptotic performance of the robust algorithm can reach the CRB under some moderate conditions and outperform the Cheng method when the location deviations exist.